Exerted influence of DES concentration in the room temperature ionic conductivity and thermal behavior of CS-LiTFSI-DES polymer electrolytes - Ramesh, Subramaniam; Shanti, R.; Morris, E.; Durairaj, R. (2010)
In this communication, effort was devoted to fabricate completely biodegradable polymer electrolytes that are environmental-friendly by utilizing com starch (CS), bis(trifluoromethanesulfonyl)imide (LITFSI) and deep eutectic solvent (DES) (synthesized from the mixture of choline chloride and urea with 1:2 ratio) by solution casting technique. The incorporation of DES in plasticizing the CS-LiTFSI matrix was valued primarily due to its capability in increasing the amorphous elastomeric phase in the polymer matrix. This is a new and versatile platform which allows high ionic conduction possessed by natural polymer based polymer electrolytes. In alien to identify the best DES composition ratio, a wide range of electrolyte compositions from 0 to 90 wt. % of DES was prepared by dissolution of DES in CA-LiTFSI system. The resultant system was characterized by total ionic conductivity measurements, ions mobility and thermal analysis. The maximum conducting sample was identified with the DES content of 80 wt. % with the conductivity value of 1.04 x 10-3 Scm-I. The stated sample was believed to have the highest ionic transport mechanism. A decreasing trend in the melting temperature of polymer electrolytes with increase DES content were visualized from the DSC analysis which suggest the complexation between the constituents that induce to structural disordemess. Relying on the TGA results, it can be visualized that the). addition of an appropriate amount of DES in CS-LiTFSI matrix capable in sustaining both of its thermal properties as being desired.